(untitled) (Theatrum historiae, 2016)
This study is focusing on the library of Franz Ferdinand and Johann Wenzel von Gallas originating from 1660 to 1719. The attention is aimed at the circumstances of the library’s development and Franz Ferdinand and his son Johann Wenzel von Gallas’ reading interests. The findings are compared to other baroque literary collection. In the conclusion there is an outline of later development of Gallas as well as the later Clam-Gallas library.